Functional Adaptation of Oromotor Functions and Aging: A Focused Review of the Evidence From Brain Neuroimaging Research - Lin, Chia-Shu (Frontiers in Aging Neuroscience, 2020)
“Practice makes perfect” is a principle widely applied when one is acquiring a new sensorimotor skill to cope with challenges from a new environment. In terms of oral healthcare, the traditional view holds that restoring decayed structures is one of the primary aims of treatment. This assumes that the patient’s oromotor functions would be recovered back to normal levels after the restoration. However, in older patients, such a structural-functional coupling after dental treatment shows a great degree of individual variations. For example, after prosthodontic treatment, some patients would adapt themselves quickly to the new dentures, while others would not. In this Focused Review, I argue that the functional aspects of adaptation—which would be predominantly associated with the brain mechanisms of cognitive processing and motor learning—play a critical role in the individual differences in the adaptive behaviors of oromotor functions. This thesis is critical to geriatric oral healthcare since the variation in the capacity of cognitive processing and motor learning is critically associated with aging. In this review, (a) the association between aging and the brain-stomatognathic axis will be introduced; (b) the brain mechanisms underlying the association between aging, compensatory behavior, and motor learning will be briefly summarized; (c) the neuroimaging evidence that suggests the role of cognitive processing and motor learning in oromotor functions will be summarized, and critically, the brain mechanisms underlying mastication and swallowing in older people will be discussed; and (d) based on the current knowledge, an experimental framework for investigating the association between aging and the functional adaptation of oromotor functions will be proposed. Finally, I will comment on the practical implications of this framework and postulate questions open for future research.